Genome-wide association study of esophageal squamous cell carcinoma in Chinese subjects identifies a susceptibility locus at PLCE1 - Wang, Li-Dong; Zhou, Fu-You; Song, Xin; Jin, Yan; Li, Jiang-Man; Kong, Guo-Qiang; Cui, Juan; Zhang, Lian-Qun; Yang, Jie-Zhi; Li, Ji-Lin; Liu, Zhi-Cai; Gao, Wen-Jun; et al. (Nature genetics, 2010)
Li Dong Wang and colleagues report a genome wide association study for esophageal squamous cell carcinoma in the Chinese population. They identify two risk loci at PLCE1 and C20orf54 . We performed a genome-wide association study of esophageal squamous cell carcinoma (ESCC) by genotyping 1,077 individuals with ESCC and 1,733 control subjects of Chinese Han descent. We selected 18 promising SNPs for replication in an additional 7,673 cases of ESCC and 11,013 control subjects of Chinese Han descent and 303 cases of ESCC and 537 control subjects of Chinese Uygur-Kazakh descent. We identified a previously unknown susceptibility locus for ESCC: PLCE1 at 10q23 ( P Han combined for ESCC = 7.46 × 10 −56 , odds ratio (OR) = 1.43; P Uygur-Kazakh for ESCC = 5.70 × 10 −4 , OR = 1.53). We also confirmed association in 2,766 cases of gastric cardia adenocarcinoma and the same 11,013 control subjects ( PLCE1 , P Han for GCA = 1.74 × 10 −39 , OR = 1.55. PLCE1 has important biological implications for both ESCC and GCA. PLCE1 might regulate cell growth, differentiation, apoptosis and angiogenesis.